Zoom : the global race to fuel the car of the future. - Carson, Iain, ....-; Vaitheeswaran, Vijay V., ....- (New York : Twelve, 2007)
A stirring call to arms urging Americans to demand that the government act now to meet the challenges of global warming and to tackle the country's addiction to oil. Carson, former industry editor of The Economist, and Vaitheeswaran, who for ten years reported on environmental and energy issues for that magazine, take to task the automakers of Detroit and Big Oil, dubbing them "dinosaurs" facing extinction unless they change their thinking soon. The authors' closeup look at the workings of the auto industry is sharp and pulls no punches. They credit Toyota with taking the lead in the race to develop the successor to the internal-combustion engine, calling the Prius a stepping stone to the car of the future. The chapters on oil trace the story of America's dependence on Mideast oil from FDR's pact with Ibn Saud of Saudia Arabia in World War II to the terror-threatened market of the present day, and they consider the serious problems now facing the Western oil giants, especially the restricted access to reserves as competition from national oil companies increases. But there's also good news, note the authors. Employing religious terminology, they envision a "Great Awakening" under way in the form of a new awareness of the need for energy reform and some specific actions being taken to achieve it. They offer engrossing stories about a variety of technology innovators and entrepreneurs with fresh ideas about clean energy, including the use of hydrogen to power cars that have clean fuel cells instead of dirty gasoline engines. The authors conclude with a manifesto stating five principles for a smart energy policy, including the necessity of individual action and a grassroots rebellion that will prompt action from the country's leaders.A timely, authoritative book written in a punchy, easy-to-read style.